Optimisation Of Ice Cream Production (Case Study "X Ice Cream" Rimbo Kedui Village Seluma Selatan District Bengkulu Province) - Bambang Sumantri; Reflis Reflis; Rahmi Yuristia; Adithya Dwi Kuntardi (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to Determine the combination of optimal production of various types of ice cream products that generate profits that are maximal in business X ice cream and determine the maximum profit at the business X ice cream with the formulation of the optimisation model, as well as knowing the sensitivity of changes in input prices and output the optimal solution is generated. This research was conducted on the business of Ice Cream X in the Village of Rimbo Kedui, South Seluma district, Seluma Regency Bengkulu Province, held in September –October 2020. The Data in this research is primary data obtained through interviews with business owners. Data analysis was performed using the analysis tools of linear programming. The results of the research show the combination that produces the maximum profit in the form of a company should manufacture ice cream in 1350 packs, chocolate ice cream in 900 packs, ice cream mango flavour 960 wraps, ice cream flavours melon 1050 wrap, and chocolate ice cream-strawberry 745 wraps. Also, do not produce more flavours of vanilla ice cream-strawberry, ice cream, vanilla chocolate. By producing such a combination, the X ice cream business will get a maximum profit of Rp. 7.710.266,-